Interpersonal skills for group collaboration : creating high-performance teams in the classroom and the workplace - Rice-Bailey, Tammy; Chong, Felicia (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This lively and engaging text introduces readers to the core interpersonal and organizational skills needed to effectively collaborate on group projects in the classroom and the workplace. Group projects are critical in preparing students for the realities of today's workplace, but many college students despise group work-often because they have not been prepared with the necessary skills to effectively collaborate. This guide teaches core collaboration skills such as active listening, interviewing, empathy, and conflict resolution. It examines the research and theory behind these skills, and provides tangible ways to practice these skills both alone and in groups. This guide can be used a supplementary text for any courses involving group projects, and will also be of interest to professionals in communication, business, and many other fields"--
Introduction -- Engaging in Conversation -- Listening -- Conveying and Monitoring Nonverbal Cues -- Practicing Empathy -- Sharing ideas -- Employing Creativity -- Managing Conflict -- Developing Self-Awareness -- Making Your Meetings Productive.
Keywords: Interpersonal relations; Cooperation; Teams in the workplace; STUDY AIDS / College Guides; BUSINESS & ECONOMICS / Business Communication / General